2012 IEEE International Symposium on Intelligent Control 2012
DOI: 10.1109/isic.2012.6398265
|View full text |Cite
|
Sign up to set email alerts
|

Indirect M-MRAC for systems with time varying parameters and bounded disturbances

Abstract: Abstract-The paper presents a prediction-identification model based adaptive control method for uncertain systems with time varying parameters in the presence of bounded external disturbances. The method guarantees desired tracking performance for the system's state and input signals. This is achieved by feeding back the state prediction error to the identification model. It is shown that the desired closed-loop properties are obtained with fast adaptation when the error feedback gain is selected proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…This is the case of unconstrained M-MRAC with time variant uncertainties, which was studied in [17].…”
Section: Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case of unconstrained M-MRAC with time variant uncertainties, which was studied in [17].…”
Section: Prediction Modelmentioning
confidence: 99%
“…In this paper, we present an adaptive control method for input constraint multi-input multioutput nonlinear dynamical systems with time varying parametric uncertainties and bounded external disturbances. The method, which was rst presented in [17], uses a prediction model to rapidly generate adaptive estimates of the system's uncertainties. It is shown that the designed controller requires no modication or tuning to guarantee tracking of a given reference model inside a region in the space of initialization errors, design parameters and external commends described by a sucient condition, which is derived based on the adaptive estimation bounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a prediction-identification model based adaptive control method was proposed for uncertain systems with timevarying parameters in the presence of bounded external disturbances, and the desired tracking performance was achieved by feeding back the state prediction error to the identification model. The desired closed-loop properties were obtained when the error feedback gain was proportional to the square root of the adaptation rate [8]. However, an apparent drift of adaptive gains may occasionally arise, eventually leading to closed-loop instability.…”
Section: State Of the Artmentioning
confidence: 99%
“…The method was extended to several class of systems in state feedback framework. [13][14][15][16] In this paper we apply the M-MRAC method to a class of uncertain single-input single-output (SISO) linear systems in output feedback framework. It is shown that the tracking errors in the output signal as well as in the input signal can be decreased as desired by a proper selection of the design parameters.…”
Section: Introductionmentioning
confidence: 99%